INVESTING IN INNOVATION: KEY STRATEGIES FOR SUCCESSFUL BUSINESS DEVELOPMENT (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
The article "Investing in Innovation: Key strategies for successful business development" provides an overview of the modern business world and its requirements for innovation, as well as examines key strategies for investing in innovation. The article discusses the concept of innovation, its importance for business, as well as methods for measuring and evaluating the effectiveness of investments in innovation. The presented material allows readers to understand which strategies and approaches can help companies successfully invest in innovation and achieve a competitive advantage in the market.